2008
DOI: 10.1111/j.1439-037x.2008.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine Improves Chilling Tolerance in Hybrid Maize

Abstract: Plant growth and development is hampered by various environmental stresses including chilling. We investigated the possibility of improving chilling tolerance in hybrid maize by glycinebetaine (GB) seed treatments. Maize hybrid (Hycorn 8288) seeds were soaked in 50, 100 and 150 mg l−1 (p.p.m.) aerated solution of GB for 24 h and were dried back. Treated and untreated seeds were sown at 27 °C (optimal temperature) and at 15 °C (chilling stress) under controlled conditions. Germination and seedling growth was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 49 publications
5
72
0
Order By: Relevance
“…In previous studies, plants treated with GB under optimal conditions showed similar results with respect to rice leaf photosynthetic rates and stomatal conductance (Farooq et al, 2008a). Application of SA did not alter leaf photosynthetic rates in mungbean (Vigna radiate L.) plants with respect to leaf photosynthetic rates.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In previous studies, plants treated with GB under optimal conditions showed similar results with respect to rice leaf photosynthetic rates and stomatal conductance (Farooq et al, 2008a). Application of SA did not alter leaf photosynthetic rates in mungbean (Vigna radiate L.) plants with respect to leaf photosynthetic rates.…”
Section: Discussionsupporting
confidence: 53%
“…Application of SA increases mobilization of reserve food materials to the grain during the grain filling process by increasing the activities of hydrolyzing and oxidative enzymes (Sawhney et al, 1979), hence increasing the number of filled grains. Application of GB increases the synthesis of compatible solutes (Farooq et al, 2008a), whereas application of SA detoxifies superoxide radicals (Bowler et al, 1992), which in turn decreases levels of ROS, thus increasing the integrity of cellular membranes. In addition, GB protects transcriptional and translational machinery, acting as a molecular chaperone in the refolding of enzymes (Rhodes & Hanson, 1993), whereas SA stabilizes trimers of heat shock transcription factors (Larkindale & Knight, 2002), thus rendering protection to membranes and enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some plant species cannot synthesize GB in sufficient amounts, and its exogenous ap-plication becomes indispensable to induce stress tolerance. GB is involved in higher plants as a defensive response to extreme conditions of salt, drought, temperature or light stress (Farooq et al 2008). It stabilizes the structures and activities of enzymes and protein complexes and maintains the integrity of membranes against the damaging effects of abiotic stresses (Sakamoto and Murata 2002).…”
mentioning
confidence: 99%
“…superoxide dismutase, catalase and enzymes of the ascorbate and glutathione cycle) (Zhang & Kirkham, 1996). Glycine betaine and SA are synthesized in the plants and play important but different, roles in preventing oxidative damage to the membranes (Bowler et al, 1992;Demiral & Turkan, 2004) and inducing theromotolerance in plants subjected to stresses (Ashraf & Foolad, 2007;Caldas et al, 1999;Farooq et al, 2008aFarooq et al, , 2008bLarkindale & Huang, 2004;Mohammed & Tarpley, 2009b;Pan et al, 2006;Raskin, 1992). The commercial availability of GB and SA provides potential crop-management options to reduce crop heat stress events.…”
Section: Plant Growth Regulatorsmentioning
confidence: 99%